Women's Tanci fiction in late imperial and early twentieth-century China - Guo, Li, 1979- (Comparative cultural studies., 2015)
In Women's Tanci Fiction in Late Imperial and Early Modern China, Li Guo presents the first book-length study in English of women's tanci fiction, the distinctive Chinese form of narrative written in rhymed lines during the late imperial to early modern period (related to, but different from, the orally performed version also called tanci). She explores the tradition through a comparative analysis of five seminal texts. Guo argues that Chinese women writers of the period position the personal within the diegesis in order to reconfigure their moral commitments and personal desires. By fashionin.